Experience with endoluminal functional luminal probe (EndoFLIP) at San Ignacio University Hospital, Bogota, Colombia - Hani, Albis (2024)
Introduction: The EndoFLIP (for its acronym in English: endoluminal functional luminal probe) is a system that measures in real time the compliance index of the gastroesophageal junction and secondary esophageal peristalsis, based on the principle of impedance planimetry. Although this technology is relatively new and its diagnostic usefulness is still being evaluated, its use in clinical practice is increasingly recognized, fundamentally in those patients where there is no conclusive manometric diagnosis of esophageal motor pathology, mainly esophagogastric junction outflow obstruction and achalasia. Objective: The aim of the present study is to describe the experience with EndoFLIP at the San Ignacio University Hospital in Bogotá, Colombia. Material and methods: Descriptive observational case series study, which included patients over 18 years of age who had undergone EndoFLIP at the San Ignacio University Hospital from 2021 to 2022, either in-hospital or outpatient, with a clear indication of performance of the study, previously discussed in the multidisciplinary Gastroenterology Board. Results: A total of 27 patients with an average age of 55 years were included in the study, of which 20 were women (74%) and 7 men (26%). The most frequent indication of the study was an inconclusive diagnosis of outflow tract obstruction identified in high-resolution esophageal manometry according to Chicago 4.0 criteria (14 patients), followed by hypercontractile esophagus (4 patients) and ineffective esophageal motility (3 patients). When evaluating the contractile response, it was found that 9 patients with an inconclusive diagnosis of outflow tract obstruction had a normal response, 3 absent and one altered; and in the patients with an inconclusive diagnosis of achalasia, one of them had a borderline contractile response and two had no response. All patients with a previous diagnosis of absent contractility had an equally absent contractile response in EndoFLIP. Conclusion: Endoluminal functional luminal imaging is a technique that evaluates biomechanical properties such as distensibility, volume, pressure and even diameters of sphincter regions such as the gastroesophageal junction, pylorus and anus. Its usefulness has been highlighted for several  indications, the most important being  manometrically inconclusive diagnoses of esophageal motor disorders such as achalasia and outflow tract obstruction, pathologies that have a significant impact on the quality of life of patients and whose diagnosis is essential to be able to provide the best treatment option.